1969
DOI: 10.12669/pjms.313.7218
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Pro Re Nata Regimen without Loading Dose Ranibizumab Injections in Retinal Vein Occlusion

Abstract: Objectives:To evaluate the effects and safety of intravitreal ranibizumab on visual acuity and anatomic results in the treatment of macular edema due to retinal vein occlusion (RVO).Methods:Forty Six eyes of 45 patients who were administered intravitreal ranibizumab because of macular edema due to Retinal Vein Occlusion (RVO) were included in this retrospective clinical study. During monthly follow-up, the best corrected visual acuity values in terms of LogMAR with The Early Treatment Diabetic Retinopathy Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Confirming that remark, mean letter gain was found to be 18.8 in patients who received three RNB injections in our study. Likewise, Unsal et al reported a VA better than 6/12 in 31.0 per cent of eyes with mean 2.1 RNB injections. That rate was 35.7 per cent in our study.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Confirming that remark, mean letter gain was found to be 18.8 in patients who received three RNB injections in our study. Likewise, Unsal et al reported a VA better than 6/12 in 31.0 per cent of eyes with mean 2.1 RNB injections. That rate was 35.7 per cent in our study.…”
Section: Discussionmentioning
confidence: 90%
“…No eyes received laser treatment in the injection groups. It offers a real‐world comparison of DEX and RNB in BRVO‐related macular oedema and the sample size is relatively sufficient compared with previous studies . Although frequent injections with regular intervals could not be given, our patients were followed closely.…”
Section: Discussionmentioning
confidence: 99%
“…The recommended dosage is 0.5 mg, 2.0 mg, and 1.25 mg for ranibizumab, aflibercept, and bevacizumab, respectively [115, 116]. Some specialists preferred a monthly injection, while others employ a treat and extend (TREX) or an as needed (pro re nata) regimen [93, 106, 117120]. A recent study reported that BRVO patients can receive good VA and central macular thickness (CMT) outcomes with a lower frequency of intravitreal ranibizumab.…”
Section: Treatmentmentioning
confidence: 99%
“…[ 22 ] Intravitreal anti-VEGF injections are a standard of care in such cases, which can be performed PRN with or without a loading dose. [ 23 24 ] Almost equal proportion of VRSI survey respondents elected to start PRN regimen from baseline (43.2%) and loading doses of three monthly injections, followed by PRN (40.2%), respectively, in the management of a fresh BRVO with CME. In a scenario when there is no response after three anti-VEGF injections and with significant capillary dropout on FA, more than half of the participants (53.3%) preferred to perform additional sectoral PRP.…”
Section: Discussionmentioning
confidence: 99%